Simultanagnosia as a cause of visual disturbance following Posterior Reversible Encephalopathy Syndrome (PRES): A case report - Niranjan K Pehere (Indian Journal of Ophthalmology, 2020)
Simultanagnosia resulting from dorsal stream dysfunction is an under recognized condition. In this case report we describe the case of a young woman who developed posterior reversible encephalopathy syndrome (PRES), and who recovered visual acuities of 20/20 in each eye, along with normal visual fields and contrast sensitivities, yet experienced persistent symptoms of perceptual dysfunction. Detailed and systematic history taking revealed consistent visual difficulties typical of dorsal stream dysfunction. After a detailed explanation of her symptomatology and training in a range of strategies to cope, the patient experienced a great improvement in her day-to-day functioning.